Role of gap junctions in breast cancer - Gakhar, Gunjan (Kansas State University, 2009)
Gap junctional intercellular channels allow the cells to communicate with each other. A breach in gap junctional intercellular communication (GJIC) affects cell growth and proliferation. In addition, many neoplastic cells exhibit a decrease in GJIC. Many factors that decrease GJIC have been shown to potentiate cancer formation. 2,3,7,8 tetrachlorodibenzo-p-dioxin (TCDD), an environmental pollutant, is a carcinogen; however, its mechanism of carcinogenicity is unclear. Therefore, we examined the effect of TCDD on GJIC in MCF-7, a human breast cell line and normal mammary epithelial cells (HMEC). TCDD showed a decrease in GJIC in MCF-7 cells caused by increased phosphorylation of gap junctional protein, Cx43. PKCα-mediated phosphorylation of Cx43 was confirmed by inhibitor studies using calphostin C. Interestingly, TCDD affected GJIC in HMEC through a novel pathway involving redistribution of Cx43 to the perinuclear membrane. Our studies suggest that TCDD causes decrease in GJIC which could potentially lead to cancer. This also indicates that if GJIC is restored it could decrease cell growth and proliferation. Therefore, we investigated the role of substituted quinolines (PQ1), shown to bind with gap junctional proteins by computational docking. The results showed that indeed PQ1 significantly increases GJIC and exerts anti-tumor effect in human breast cancer cells compared to control without treatment or HMEC. We found an increase in GJIC, growth attenutation and increased apoptosis in T47D human breast cancer cell line. Our studies suggest that PQ1 is a novel gap junctional activator causing a decrease in tumor growth. Since PQ1 alone is effective in decreasing tumor growth in breast tumors, we proposed to test its efficacy with the current drug of choice for breast cancer, tamoxifen. The combinational treatment of tamoxifen and PQ1 showed a significant decrease in cell viability, increase in BAX (Bcl2-associated X), and, increase in caspase 3 activation compared to individual treatments. Hence, combinational treatment of PQ1 and tamoxifen can potentiate decrease in tumor growth. In conclusion, downregulation of gap junctions can potentiate tumor growth while restoration of GJIC can induce apoptosis and decrease tumor growth.
Keywords: Breast Cancer; Gap Junctions; Biology, Veterinary Science (0778)